Combined associations of cardiorespiratory fitness and grip strength with non-high-density lipoprotein cholesterol concentrations among Japanese children and adolescents - Tetsuhiro Kidokoro; Masashi Miyashita (Japanese Society of Physical Fitness and Sports Medicine, 2020)
The present study aimed to examine the associations between cardiorespiratory fitness and muscular strength (both independently and combined) and non-high-density lipoprotein cholesterol (non-HDL-C) concentrations in 652 Japanese children and adolescents (mean ± SD, 11.0 ± 1.5 years). Fasting blood tests were conducted to measure total cholesterol, HDL-C, triglyceride, and low-density lipoprotein cholesterol concentrations. Cardiorespiratory fitness was determined using the 20 m shuttle run test (SRT), and muscular strength was obtained from grip strength (GS) tests. Relative GS, which was defined as absolute GS divided by body mass index (BMI), was computed. Cardiorespiratory fitness was inversely associated with non-HDL-C after adjusting for age, gender, and BMI (β = -0.102, p < 0.05). However, this association was diminished after adjusting for relative GS. In contrast, relative GS was inversely associated with non-HDL-C, and this remained significant even after adjusting for age, gender, BMI, and cardiorespiratory fitness (β = -0.162, p < 0.05). There was a significant interactive effect (20 m SRT*relative GS) on non-HDL-C after adjusting for age, gender, BMI (β = -0.122, p < 0.05). Additionally, combined analysis showed that children and adolescents with both low SRT and GS demonstrate the highest non-HDL-C concentrations compared with their counterparts, suggesting that the effects of cardiorespiratory fitness and muscular strength were additive. In conclusion, enhancing muscular fitness may be a primary target through which non-HDL-C concentrations can be regulated, particularly for children and adolescents with low cardiorespiratory fitness.